Harnessing Health Technology Assessment in Latin America and the Caribbean: Keeping the Region on Course - Ursula Giedion; Manuel Antonio Espinoza; Pamela Góngora-Salazar; Abha Mehndiratta; Dan Ollendorff (Taylor & Francis Group, 2023)
Latin America and the Caribbean has made significant progress toward universal health coverage (UHC), but health spending efficiency, equity, and sustainability remain major challenges-and progress is hindered by the difficult macroeconomic context. Health technology assessment (HTA) can make resource allocation more efficient and equitable when systematically used to inform coverage decisions. We highlight five considerations that need to be taken into account to realize the full potential of HTA in the LAC region: i) explicitly link HTA to decision-making and anchor it in legal frameworks, ii) systematically incorporate the opportunity cost as a core principle into HTA activities informing coverage decisions, iii) make the internationally available evidence more fit for purpose for low- and middle-income countries (LMICs), iv) incorporate pragmatism as a key principle of HTA activities in the region, and v) institutionalize the monitoring of HTA processes and results.